PENGARUHE-BOOKTERHADAPLITERASIPESERTA DIDIK DI SEKOLAH DASAR - Nur Afifah; Muhammad Haffiz; Nadiatul Jannah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
The use of e-books in elementary school education has emerged as a significantinnovation in improving students' reading literacy. This article examines the influence of e-books on the literacy of elementary school students, drawing on relevant literature and recent empirical research. Literacy, defined broadly as the ability to read, write, and think critically, is a fundamental competency that must be developed from an early age. Indonesia's literacy levels remain low in international comparisons,makingthesearchforeffectiveinterventionsparticularlyimportant.E-books,asdigitalreadingmedia,offerinteractivefeaturessuchascolorfulillustrations, audio support, and accessible content that can enhance students' motivation and comprehension. Research consistently shows that e-book use leads to statistically significant improvements in reading literacy scores compared to conventional methods. This study adopts a literature review approach, synthesizing findings from multiple studies to conclude that e-books are an effective and practical tool for improving literacy in elementary schools. Recommendations for teachers and policymakers are discussed.